Therapeutic drug monitoring of mycophenolate mofetil in pediatric patients: novel techniques and current opinion. (1st February 2021) - Ehren, Rasmus; Schijvens, Anne M.; Hackl, Agnes; Schreuder, Michiel F.; Weber, Lutz T.
ABSTRACT: Introduction : Mycophenolate mofetil (MMF) is an ester prodrug of the immunosuppressant mycophenolic acid (MPA) and is recommended and widely used for maintenance immunosuppressive therapy in solid organ and stem-cell transplantation as well as in immunological kidney diseases. MPA is a potent, reversible, noncompetitive inhibitor of the inosine monophosphate dehydrogenase (IMPDH), a crucial enzyme in the de novo purine synthesis in T- and B-lymphocytes, thereby inhibiting cell-mediated immunity and antibody formation. The use of therapeutic drug monitoring (TDM) of MMF is still controversial as outcome data of clinical trials are equivocal. Areas covered : This review covers in great depth the existing literature on TDM of MMF in the field of pediatric (kidney) transplantation. In addition, the relevance of TDM in immunological kidney diseases, in particular childhood nephrotic syndrome is highlighted. Expert opinion : TDM of MMF has the potential to optimize therapy in pediatric transplantation as well as in nephrotic syndrome. Limited sampling strategies to estimate MPA exposure increase its feasibility. Future perspectives rather encompass approaches reflecting total immunosuppressive load than single drug TDM.